ҚАРАҚАЛПАҚ ГҮРРИҢИНДЕ ХРОНИКАЛЫҚ СЮЖЕТ ҲӘМ АВТОРЛЫҚ ШЕБЕРЛИК МӘСЕЛЕСИ - Ктайбекова, З.К. (ILIM hám JÁMIYET, 2018)
The article is devoted to the study of the chronical plot in the poetics of modern Karakalpak story. The author comes to the important scientific-theoretical conclusions by analyzing some of the stories of Karakalpak writers.